1998
DOI: 10.1016/s1387-1811(98)00148-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and neutralizing properties of a natural zeolite/Na2CO3 composite material

Abstract: A new zeolitic active principle called NZ* has been obtained, the neutralizing properties of which are better than those of its predecessor, Neutacid N. The new product is the result of hydrothermal transformations applied to purified natural clinoptilolite. NZ* and other related products have been characterized physically and chemically using atomic emission spectroscopy with inductively coupled plasma, X-ray fluorescence analysis, X-ray diffraction, IR spectroscopy, neutralizing capacity in the presence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…This was explained with its ion exchange property. In the other study reported by Rivera et al [13] the zeolitic material was used as an antacid for gastric disturbances. It was found that both natural zeolitic material and its Na 2 CO 3 treated form raised the pH to the accepted range for gastric disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…This was explained with its ion exchange property. In the other study reported by Rivera et al [13] the zeolitic material was used as an antacid for gastric disturbances. It was found that both natural zeolitic material and its Na 2 CO 3 treated form raised the pH to the accepted range for gastric disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was reported to decrease the deposition of radioactive compounds in animals administered to the contaminated feed and it reduced oxidative stress in animals after partial hepatectomy [15,16]. Purified natural clinoptilolite was reported to be harmless to the human body [17] and was used as antidiarrheaic drug [18] and as antiacid agent for humans suffering from the hyperacidity without showing any toxic or biological hazard [19,20]. A novel use of micronized clinoptilolite as a potential adjuvant in anticancer therapy was reported [21].…”
Section: Introductionmentioning
confidence: 99%
“…Available data primarily focus on using zeolites as drugs or drug supports [18,19,22]. However, investigations of natural zeolite's behavior only in simple buffer solutions or in batch experiments for medical purposes will be insufficient to reflect the complicated digestion media where there were also digestive enzymes or bile salts.…”
Section: Introductionmentioning
confidence: 99%
“…Clinoptilolite-rich natural zeolites have been applied for drug delivery purposes Rivera et al, 1998Rivera et al, , 2003Concepción-Rosabal et al, 1997Lam et al, 1998;Carballo et al, 2001;Farías et al, 2003;Rivera and Farías, 2005) and as a potential adjuvant in anticancer treatment (Seidel et al, 1997;Parlat et al, 1999;Pavelic et al, 2001Pavelic et al, , 2002. Recently, the clinoptilolite-rich natural zeolite from Western Anatolia and its acid-modified and ionexchanged forms were investigated for its thermal stability, antibacterial activity, water vapor, carbon dioxide and carbon monoxide adsorption and diffusion properties (Top, 2001;Top and Ülkü, 2004;Ülkü, 2004, 2008;Narin, 2001;Narin et al, 2004;Ülkü, 2007, 2008).…”
Section: Introductionmentioning
confidence: 99%